Analisis Mikrostruktur Partikel Zirkoniakalsia-silika (ZrO 2 -CaO-SiO ) Dari Pasir Zirkon Alam Indonesia Menggunakan Metode Spray Pyrolysis - Elin Karlina; Nina Djustiana; I Made Joni; Renny Febrida; Camellia Panatarani; Akhyar Dyni Zakyah (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2017)
Indonesian Natural Sand, Zircon, is an Indonesia’s natural resource that contains zirconia, silica, titania and alumina. In Dentistry, zirconia as one of the content in natural zircon sand, have the potential to be the material for filler composites. The purpose of this research was to analyze the Zirconia-Calcium-Silicate Particle (ZrO2CaO-SiO2) synthesized from Indonesia natural sand, zircon, in microstructural way. Methods: By synthesizing ZirconiaCalcium-Silicate particle (ZrO2-CaO-SiO2) from Indonesia natural zircon sand, using spray pyrolysis method. A precursor solution that is used consists of zirconil nitrate (Zr (NO3) 2), sodium silicate (Na2SiO3), and calcium hydroxide (Ca (OH) 2). Variations in the temperature of the reactor that are used were 4000C, 4500C, and 5000C with a feed rate of 6 L / min and a piezoelectric frequency of 1.7 MHz. Result showed that the better content in zirconia-calcium-silicate is the one that was synthesized at a temperature of 4500C, based on the results of EDS, SEM and XRD. The composition that is obtained in the zirconia-calcium-silicate particle has a ratio of 1: 14: 4 with the size of 500-1000nm, and has a tetragonal crystal zirconium silicate structure and dicalcium monoclinic silicate. From this research it can be concluded that the result that was synthesized at a temperature of 4500C is adequate to use as a filler based on the characterization result of SEM and XRD.